Self emulsifying drug delivery system (SEDDS): a review - Sharma, P. K.; Kar, Mousumi; Jain, D. K. (Creative Pharma Assent, 2014)
Self-emulsifying drug delivery system is mixture of oils, surfactant, cosurfactant, which are emulsified in aqueous media under condition of gentle stirring and digestive motility that would be encountered in the gastrointestinal tract. SEDDS is one of the approaches to improve the oral bioavailability of the hydrophobic drugs. The liquid SEDDS can be converted into solid dosage form without affecting drug release property. Due to its small size the micro/nano emulsified drug can easily be absorbed through lymphatic pathways thereby bypassing the hepatic first-pass effect. The main benefit of this approach is that pre-dissolving the compound overcomes the initial rate limiting step of particulate dissolution in the aqueous environment within the GI tract. Self-emulsification occurs when entropy changes that favor dispersion is greater than the energy required to increase the surface area of the dispersion.